Optimization and validation of process parameters via RSM for minimizing use of resources to generate electricity from a DEFC - Choudhary A.K.; Pramanik H. (My University, 2025)
In this study, the response surface methodology (RSM) was applied to design the Box-Behnken design (BBD) experiments and optimize the interactive effects of major operating parameters of direct ethanol fuel cells (DEFCs) for achieving the maximum power density. The main effective operating parameters of DEFCs like ethanol concentration, anode electrocatalyst loading, and operating temperature were selected as independent variables in BBD while the power density was considered to be the response function under investigation. The Nafion 117 membrane as solid electrolyte and synthesized Pt-Ru-Re (1:1:0.5)/f-MWCNT as anode and commercial Pt/CHiSPEC as cathode electrocatalysts were used, respectively. The individual and combined effects of independent variables on the maximum power density of DEFC were also examined. A second-order model was established according to the RSM results and statistically validated by analysis of variance (ANOVA) to provide a satisfactory description of the experimental data. The maximum peak power density of 22.10 mW/cm2 was obtained by RSM modeling and the same was validated experimentally using the optimum condition of a 2.03 M ethanol concentration, 1.14 mg/cm2 anode electrocatalyst loading, and 79.48°C operating temperature. The validation of the model showed that the experimentally measured value of the highest power density achieved under optimized conditions (21.53 mW/cm2) was very close to the computed value (22.10 mW/cm2) by the model. The optimization results via the RSM demonstrated that the power density of DEFC was significantly affected by operating cell temperature, followed by anode electrocatalyst loading and ethanol concentration. © 2021 John Wiley & Sons Ltd.